An evaluation of organizational change in the Housing & Development Board - Tan, Ai Ling (2010)
The need for change is constant in the current business environment. As customers become more informed and demanding, organizations must undergo transformation to meet customers’ expectation. While organizations understand the need for change, organizational transformation is never an easy task.